IBN KHALDUN MODEL ON POVERTY: THE CASE OF ORGANIZATION OF ISLAMIC CONFERENCE (OIC) COUNTRIES - Ahlis Fatoni; Sebastian Herman; Adam Abdullah (Journal of Islamic Monetary Economics and Finance, 2019)
If we consider the state of the world economy, especially in the OIC countries, some countries have to struggle in dealing with the problems of poverty. Hypothetically, the wealth of natural resources is potentially in the welfare of the population, but the facts on the ground say the situation is another in which it is far from being well- being. This study aims to analyze poverty in OIC countries by using a development model proposed by Ibn Khaldun. The model consists of six variables: human resource variable (proxy HDI), the variable role of government (proxy government spending in education and health), variable of development (proxy foreign direct investment), state assets variable (proxy for GDP/capita), justice variable (gini index proxy) and sharia variable (a proxy perception index of corruption). This study uses panel data regression analysis with nine object OIC member countries (Indonesia, Malaysia, Egypt, Azerbaijan, Kazakhstan, Tajikistan, Kyrgyzstan, Turkey and Benin) over the years from 2010 to 2016. The results showed that the variables of development model Ibn Khaldun significant effect on poverty in OIC countries is development variable, the variable role of government (proxy for government spending in health sector), justice variable, wealth nation variable and control variables (unemployment). While the role of government variable (proxy government spending in the education sector), HR variables and sharia variables not significant. From these studies, it can be concluded that not all the variables of development model Ibn Khaldun significant effect on poverty in OIC countries.